Effects of government assistance on rural Bumiputra entrepreneurs in Selangor / Azizul Azmi Azhar - Azhar, Azizul Azmi (Faculty of Business and Management, 2004)
In order to face the waves of globalization, bumiputra entrepreneurs especially from the rural area, having problem to survive in the market. Selangor State Government has develop programs to assist the entrepreneurs to gain by assets, technical and promoting their product. The objectives to the studies are (1) To examine the profile of the Bumiputra entrepreneurs in study are any association or relationship between types of entrepreneurs and government assistance activities, (2) To examine entrepreneurs' feedback after they have participates in government assistance programs. (3) To identify the major effects of government assistance operation of Bumiputra businesses that received and participate in the UPENS programs. This paper consists of 6 chapters, which explain the subject matter by stages. Chapter 1 explains of the background and introduction of the research. Chapter 2 is explaining for literature review, which related to the subject studied and theoretical framework where guide the research flow and progress. Chapter 3 discuss about the methods and s3mpling techniques use for the research. The findings discuss in Chapter 4 regard to the problem statement and objective of the study, while Chapter 5 contain the conclusion and recommendation given by the researcher. Data coded and analyze using Statistical Package for Societal Science. Appendices and bibliography attached are the relevant reference use for this study.